Analisis Perbandingan Tingkat Kebisingan Kabin Pada Mitsubishi Destinator Varian Sunroof dan Non-Sunroof Menggunakan Sound Level Meter - Faiz Arkan Yulianto; Yusep Sukrawan; Ridwan Adam M Noor; Tatang Permana; Gilang Ciptadi Mahatkarsa (CV. ALIM'SPUBLISHING, 2026)
This study aims to analyze and compare the cabin noise levels of the Mitsubishi Destinator Ultimate variant (sunroof) and Exceed variant (non-sunroof) under various driving speed conditions. Measurements were conducted using a Sound Level Meter inside the cabin at idle, 10, 30, 50, 70, 90, and 100 km/h. Results indicate that the Ultimate (sunroof) variant consistently produces higher noise levels than the Exceed (non-sunroof) variant across all speed variations. The largest noise difference was recorded at 100 km/h at 6.50 dB, while the smallest occurred at idle at 0.05 dB. Noise levels in both variants increased significantly with increasing speed, with the sunroof variant reaching 70.00 dB and the non-sunroof variant reaching 63.50 dB at 100 km/h. This difference is attributed to gaps and seals in the sunroof panel, which allow greater noise penetration from the external environment.